Innovative E-Module Development Through Flipped Book and Employability Skill Learning Integration: Advancing Competency Spa Therapy in Vocational High School - Murni Astuti; Rahmiati Rahmiati; Siska Miga Dewi; Arasinah Kamis; Rahmat Desman Koto; Adisty Akhoma Ummah (JETL (Journal of Education, Teaching and Learning), 2025)
This research presents the development and implementation of an innovative e-module that integrates flipped book technology with employability skills learning for body spa material in a Vocational High School. Using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4, this study examines the relationships between Integrated E-Modules, Learning Motivation, Self-Efficacy, Body SPA Skills, and Employability Skills. Data were collected from 64 vocational high school students specialising in the Body Spa subject (32 in the experimental group and 32 in the control group) using validated instruments. Results show that Integrated E-Modules significantly enhance students’ learning motivation and Self-Efficacy, with the experimental group demonstrating a 21.6% increase in skills compared to the control group (7.7%). Self-efficacy proved to be a key mediator in the relationship between Integrated E-Modules and Body Spa  Skills, while Learning Motivation did not show a significant mediating role. This research contributes to educational technology literature by identifying the psychological mechanisms underlying the effectiveness of learning technology in supporting quality education in practical vocational fields.